A retrospective analysis of the need for on-site emergency physician presence and mission characteristics of a rural ground-based emergency medical service - Josef Michael Lintschinger; Daniel Laxar; Lorenz Kapral; Stefan Ulbing; Thomas Glock; Sybille Behrens; Christoph Frimmel; Reinhold Renner; Daniel Alexander Klaus; Harald Willschke; Christina Hafner (BMC Emergency Medicine, 2024)
Abstract Background This study aimed to address the challenges faced by rural emergency medical services in Europe, due to an increasing number of missions and limited human resources. The primary objective was to determine the necessity of having an on-site emergency physician (EP), while the secondary objectives included analyzing the characteristics of rural EP missions. Methods A retrospective study was conducted, examining rural EP missions carried out between January 1st, 2017, and December 2nd, 2021 in Burgenland, Austria. The need for physical presence of an EP was classified based on the National Advisory Committee for Aeronautics (NACA) score into three categories; category A: no need for an EP (NACA 1–3); category B: need for an EP (NACA 1–3 along with additional medical interventions beyond the capabilities of emergency medical technicians); and category C: definite need for an EP (NACA 4–7). Descriptive statistics were used for analysis. Results Out of 16,971 recorded missions, 15,591 were included in the study. Approximately 32.3% of missions fell into category A, indicating that an EP’s physical presence was unnecessary. The diagnoses made by telecommunicators matched those of the EPs in only 52.8% of cases. Conclusion The study suggests that about a third of EP missions carried out in rural areas might not have a solid medical rationale. This underscores the importance of developing an alternative care approach for these missions. Failing to address this could put additional pressure on already stretched EMS systems, risking their collapse.